Intelligence and state surveillance in modern societies : an international perspective - Lemieux, Frédéric, 1973- (Emerald Publishing Limited, 2018)
Often described as 'two solitudes', law enforcement and national security intelligence agencies engage in intensive collaboration to address both international and domestic threats. This situation has blurred the lines between interior and exterior security; common crime and crime against the state; civil liberties, privacy, and intrusive surveillance activities; strategic national security intelligence and operational military intelligence requirements.National and local law enforcement agencies now conduct intelligence operations against international terrorist groups while national security intelligence organizations infiltrate organized crime and intercept citizens' communications on a daily basis. Other important trends are reshaping the state's surveillance and intelligence apparatus in modern societies, including the use of cyberspace for information collection, the expansion of surveillance technology penetrating citizens' everyday life, and the rise of the private sector as a primary surveillance facilitator or third party in national security intelligence collection and dissemination.This book will be of interest to those seeking to understand the intelligence environment in modern times, providing a broad understanding of current and emerging issues related to intelligence activities and offers a unique way of thinking about contemporary challenges in this field.